STRATEGI PENANGGULANGAN KEMISKINAN DI MADURA: ANALISIS REGRESI DATA PANEL - Zulkarnain, Rahmat; Muhlisin, Muhlisin; Hidayat, Nurul; Awan, Edi (Jurnal Oportunitas : Ekonomi Pembangunan, 2025)
This research aims to evaluate the influence of gross regional domestic product, economic growth, and human development index on poverty levels in four Madura districts: Bangkalan, Sampang, Pamekasan, and Sumenep. We analyze secondary data, including annual data from 2014-2023, using the panel data regression method. The research results show that gross regional domestic product has a significant positive influence on poverty levels, indicating that increasing economic activity can increase poverty due to potential inequality in economic distribution. Conversely, research demonstrates a significant negative impact of economic growth and the human development index on poverty levels. This means that increasing economic growth and human development can effectively reduce the level of poverty in Madura. The policy implications necessitate the implementation of more inclusive strategies to promote equitable distribution of economic benefits throughout the region and underscore the significance of investing in human development to enhance the quality of life and economic prospects of Madurese individuals.